2019
DOI: 10.1002/cpt.1571
|View full text |Cite
|
Sign up to set email alerts
|

Next‐Generation DILI Biomarkers: Prioritization of Biomarkers for Qualification and Best Practices for Biospecimen Collection in Drug Development

Abstract: The diagnosis and management of drug-induced liver injury (DILI) remains a challenge in clinical trials in drug development. The qualification of emerging biomarkers capable of predicting DILI soon after the initiation of treatment, differentiating DILI from underlying liver disease, identifying the causal entity, and assigning appropriate treatment options after DILI is diagnosed are needed. Qualification efforts have been hindered by lack of properly stored and consented biospecimens that are linked to clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 71 publications
0
20
0
1
Order By: Relevance
“…Several manuscripts contained more specific examples, where the safety of the collected specimens or the operator has improved through novel protocols [9] , [16] , [34] . Such technological innovation positively impacts biospecimens' handling and, consequently, on preserving biological indicators [17] or particular cell types [21] , [22] , [26] , [27] . The concept of safety of biological samples extends beyond the immediate collection and handling of biological material and onto the long-term storage conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several manuscripts contained more specific examples, where the safety of the collected specimens or the operator has improved through novel protocols [9] , [16] , [34] . Such technological innovation positively impacts biospecimens' handling and, consequently, on preserving biological indicators [17] or particular cell types [21] , [22] , [26] , [27] . The concept of safety of biological samples extends beyond the immediate collection and handling of biological material and onto the long-term storage conditions.…”
Section: Resultsmentioning
confidence: 99%
“…First, the power of this result is limited due to the small number of subjects, eight subjects per group. Furthermore, although the Food and Drug Administration of the United States has indicated that miR‐122 could be studied further as a biomarker of drug‐induced liver injury, it still requires further and thorough validation 34 . Actually, from the safety data of a clinical development report, it is reported that up to 18.8% of subjects presented liver enzyme elevation after administration of revaprazan 35 and that of tegoprazan was less than 1% 13 …”
Section: Discussionmentioning
confidence: 99%
“…The authors also describe a case of a patient with rhabdomyolysis who developed elevations in AST, ALT, and creatine kinase, while GLDH remained normal until the patient developed hypoxia-induced liver injury [45]. Roth et al reviewed the literature on emerging serum biomarkers of DILI specifically, including GLDH [46]. They highlight the potential advantages of GLDH as a biomarker including no differences in levels based on age or gender, and little intra-subject and inter-subject individual variability in several studies.…”
Section: Serum Biomarkersmentioning
confidence: 99%